Is assessment of oviposition sites using conspecific larval cues a general mechanism in aphidophagous ladybirds (Coccinellidae)?. (27th June 2016) - Magro, A.; Hill, M. C.; Gomez, M.‐C.; Hemptinne, J.‐L.
Abstract: Aphidophagous ladybirds of the Coccinellinae subfamily are deterred from oviposition in the presence of chemical cues deposited by conspecific larvae, therefore avoiding the detrimental effects of competition and cannibalism to their offspring. However, it is still unknown whether aphidophagous species from other Coccinellidae subfamilies similarly behave. Here, we investigate this question for species of the Scymninae subfamily. A GC‐MS analysis of Scymnus interruptus (Goeze) larval tracks shows that larvae deposit a cocktail of hydrocarbons containing at least five branched‐chain alkanes. Furthermore, our experiments on the oviposition behaviour of S. interruptus and S. nubilus (Mulsant) in the presence of conspecific larval tracks and of conspecific larval wax covering Scymninae larvae show that females do not refrain from ovipositing in the presence of these larval cues. We recommend that more attention is paid to the role of Scymnus spp. in the regulation of aphids because their oviposition strategy might strengthen aphid suppression in agrosystems.